Navigating Arabic Language Education in Indonesia: Challenges, Methods, and Roles of Teacher Competencies - Ummah, Vina Rohmatul; Albshkar, Hajer (Al-Fusha : Arabic Language Education Journal, 2025)
Arabic language education in Indonesia plays an important role in supporting Islamic understanding and expanding access to Arabic-language literature. However, the effectiveness of learning Arabic faces various challenges, especially in terms of teaching methodology, teacher competence, and limited learning duration. This study aims to identify the factors that affect the quality of Arabic language learning and formulate innovative strategies to improve it. The method used is qualitative research with a literature review approach. The results of the study show that the main challenges faced are limited learning time, lack of innovation in teaching methods, and lack of teaching competence in utilizing technology. This study proposes the use of interdisciplinary methods that combine technology, educational psychology, and applied linguistics as solutions to improve learning effectiveness. In addition, improving the competence of teachers through more intensive training is also considered crucial in facing learning challenges in the digital era. It is hoped that this research can contribute to the development of Arabic language education in Indonesia which is more adaptive to the times Arabic Language Education, Learning Methods, Teacher Competence, Educational Technology, Learning Innovation. Pendidikan bahasa Arab di Indonesia memainkan peran penting dalam mendukung pemahaman Islam dan memperluas akses ke sastra berbahasa Arab. Namun, efektivitas pembelajaran bahasa Arab menghadapi berbagai tantangan, terutama dalam hal metodologi pengajaran, kompetensi guru, dan durasi pembelajaran yang terbatas. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang mempengaruhi kualitas pembelajaran bahasa Arab dan merumuskan strategi inovatif untuk meningkatkannya. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan tinjauan pustaka. Hasil penelitian menunjukkan bahwa tantangan utama yang dihadapi adalah keterbatasan waktu belajar, kurangnya inovasi dalam metode pengajaran, dan kurangnya kompetensi mengajar dalam memanfaatkan teknologi. Penelitian ini mengusulkan penggunaan metode interdisipliner yang menggabungkan teknologi, psikologi pendidikan, dan linguistik terapan sebagai solusi untuk meningkatkan efektivitas pembelajaran. Selain itu, peningkatan kompetensi guru melalui pelatihan yang lebih intensif juga dinilai krusial dalam menghadapi tantangan pembelajaran di era digital. Diharapkan penelitian ini dapat berkontribusi dalam perkembangan pendidikan bahasa Arab di Indonesia yang lebih adaptif dengan perkembangan zaman. Pendidikan Bahasa Arab, Metode Pembelajaran, Kompetensi Guru, Teknologi Pendidikan, Inovasi Pembelajaran